Focusing the Neuroscience and Societal Implications of Cognitive Enhancers. Issue 2 (23rd September 2016) - Savulich, G; Piercy, T; Brühl, AB; Fox, C; Suckling, J; Rowe, JB; O'Brien, JT; Sahakian, BJ
Abstract : Cognitive enhancement can benefit the individual and society, but also has associated risks and ethical concerns. Cognitive‐enhancing drugs are used in the treatment of neuropsychiatric disorders. Nonpharmacological strategies are also emerging, which have the potential to improve motivational deficits associated with neuropsychiatric symptoms and should be prioritized for development. The increasing lifestyle use of "smart" and other drugs indicates the desire for healthy people to improve themselves. Safety and ethical implications are discussed.